Impact of Health Information System on Patient Care & Treatment: A Study on Selayang Hospita - Takhti, Hesamaddin Kamal Zadeh (2010)
The research focuses on the internal users of HIS who are the nurses themselves. Studying their views is very important and can be effective in the development of patient care. The purpose of this research is to investigate the influences of Health Information Systems on patient care at Selayang Hospital. This study is a basic research, which has been conducted with a descriptive cross-sectional method that proves the research variables were measured essentially at one point in time.